ANALYZING THE ROLE OF IPPA RIAU CHAPTER IN FACILITATING HIV REFERRAL SERVICES FOR FEMALE SEX WORKERS IN PEKANBARU - Simanjuntak, Harapan Tua Ricky Freddy; Saumitri, Nadila; Octavia, Icha (FISIP Universitas Malikussaleh, 2025)
This study aims to analyze the role of PKBI Riau in referring Female Sex Workers (FSWs) to Voluntary Counseling and Testing (VCT) HIV services in Pekanbaru. Using a qualitative descriptive approach, data were collected through interviews and program documentation. The analysis refers to Zubaedi's (2005) NGO role theory, which includes facilitative, educational, technical, and representative roles. The results showed that PKBI Riau successfully connected FWs with health services through a personal approach, building trust, and providing structured referrals. The program even exceeded its target, with 1,759 FWs successfully undergoing HIV testing. This success shows PKBI Riau's ability to reach marginalized groups who have difficulty accessing formal services. However, the study also found that follow-up treatment for FWs who were detected with HIV still needs to be strengthened so that continuity of services can be maintained. In conclusion, NGOs such as PKBI Riau play an important role as strategic partners of the government in providing public services, especially for vulnerable groups who are often marginalized by the formal health system, so that collaboration with NGOs can increase the effectiveness of public health programs.